Investigating microstructure evolution of lithium metal during plating and stripping via operando X-ray tomographic microscopy - Matthew Sadd; Shizhao Xiong; Jacob R. Bowen; Federica Marone; Aleksandar Matic (Nature Communications, 2023)
Understanding the plating and stripping behaviours of lithium metal is crucial for high-energy battery development. Here, authors track these electrochemical processes in real time by an operando synchrotron X-ray tomographic microscopy, revealing the formation of inactive lithium microstructures.